1987
DOI: 10.1136/bmj.295.6597.521
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular effects of training for a marathon run in unfit middle aged men.

Abstract: The effects of a 30 week exercise programme on serum lipid values, blood pressure, and cardiac function were assessed in a group of sedentary men aged 35-50 training for their first marathon. Mean serum cholesterol concentration (n=33) fell by 12% from 6-54 (SE 0.18) to 5-76 (0-15) mmol/l (mean fall mmol/l; 95% confidence interval 0-52 to 1-04 mmoVIl), serum triglyceride concentration (n=33) by 22% from 156 (0.17) to 1-21 (0-09) mmol/l (mean fall 0 34 mmol/l; 95% confidence interval 0-12 to 056 mmol/l), and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

1988
1988
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 14 publications
0
9
1
Order By: Relevance
“…Contro versy exists concerning left ventricular end-diastolic vol ume during dynamic exercise. Our results seemed to indicate a negligible increase in EDVI during exercise in athletes tested in a supine position, as reported by other studies [8,15], in contrast to others [16,17]. In un trained healthy subjects the increase in EF seems to be associated with an increased end-diastolic volume simi lar at both E-I and E-II [5]; other authors [13,14] report a raised end-diastolic volume only during the E-I.…”
Section: Methodscontrasting
confidence: 53%
“…Contro versy exists concerning left ventricular end-diastolic vol ume during dynamic exercise. Our results seemed to indicate a negligible increase in EDVI during exercise in athletes tested in a supine position, as reported by other studies [8,15], in contrast to others [16,17]. In un trained healthy subjects the increase in EF seems to be associated with an increased end-diastolic volume simi lar at both E-I and E-II [5]; other authors [13,14] report a raised end-diastolic volume only during the E-I.…”
Section: Methodscontrasting
confidence: 53%
“…The eVects of exercise training on weight loss in obese cardiac subjects are disappointing, 84 but some controlled trials of cardiac rehabilitation have shown a weight loss in the treated group. 85 However, a failure to reduce body weight may be due to an increase in lean muscle mass rather than a failure to reduce body fat, 86 and this has also been found in controlled trials. 87 If the patient takes a great deal of exercise, equivalent to running 15 or more miles a week, weight loss is likely.…”
Section: Weight Lossmentioning
confidence: 99%
“…Longitudinal studies of individuals exercising on a recreational basis have yielded less marked results, which are often difficult to interpret due to confounding factors like length of the training period, intensity and form of the training programme and diet or weight loss of the individuals under investigation (14)(15)(16)(17)(18)(19)(20). Furthermore, most of these studies are restricted to either exercising males or -to a far lesser extent -exercising females (17)(18)(19)(20). The present study is designed to investigate the effects of a prolonged training programme of moderate intensity on the lipid status in a group of previously sedentary males and females, while keeping other habitual factors constant.…”
Section: Introductionmentioning
confidence: 99%